MSRE-HTPrimer: a high-throughput and genome-wide primer design pipeline optimized for epigenetic research. Issue 1 (December 2016) - Pandey, Ram; Pulverer, Walter; Kallmeyer, Rainer; Beikircher, Gabriel; Pabinger, Stephan; Kriegner, Albert; Weinhäusel, Andreas
Abstract Background Methylation-sensitive restriction enzymes—polymerase chain reaction (MSRE-PCR) has been used in epigenetic research to identify genome-wide and gene-specific DNA methylation. Currently, epigenome-wide discovery studies provide many candidate regions for which the MSREqPCR approach can be very effective to confirm the findings. MSREqPCR provides high multiplexing capabilities also when starting with limited amount of DNA-like cfDNA to validate many targets in a time- and cost-effective manner. Multiplex design is challenging and cumbersome to define specific primers in an effective manner, and no suitable software tools are freely available for high-throughput primer design in a time-effective manner and to automatically annotate the resulting primers with known SNPs, CpG, repeats, and RefSeq genes. Therefore a robust, powerful, high-throughput, optimized, and methylation-specific primer design tool with great accuracy will be very useful. Results We have developed a novel pipeline, called MSRE-HTPrimer, to design MSRE-PCR and genomic PCR primers pairs in a very efficient manner and with high success rate. First, our pipeline designs all possible PCR primer pairs and oligos, followed by filtering for SNPs loci and repeat regions. Next, each primer pair is annotated with the number of cut sites in primers and amplicons, upstream and downstream genes, and CpG islands loci. Finally, MSRE-HTPrimer selects resulting primer pairs for all target sequences based on a custom quality matrix defined by the user. MSRE-HTPrimer produces a table for all resulting primer pairs as well as a custom track in GTF file format for each target sequence to visualize it in UCSC genome browser. Conclusions MSRE-HTPrimer, based on Primer3, is a high-throughput pipeline and has no limitation on the number and size of target sequences for primer design and provides full flexibility to customize it for specific requirements. It is a standalone web-based pipeline, which is fully configured within a virtual machine and thus can be readily used without any configuration. We have experimentally validated primer pairs designed by our pipeline and shown a very high success rate of primer pairs: out of 190 primer pairs, 71 % could be successfully validated. The MSRE-HTPrimer software is freely available fromhttp://sourceforge.net/p/msrehtprimer/wiki/Virtual_Machine/ as a virtual machine.